(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the relevance and importance of developing independent learning skills in the educational process in the context of the rapid development of artificial intelligence technologies. In the modern digital environment, artificial intelligence-based platforms, educational programs and interactive tools serve as an important factor in the formation of students’ competencies in independent knowledge acquisition, information search, sorting and analysis. The article highlights the issues of strengthening students’ critical thinking, independent problem solving, creative approach and self-development skills through the effective use of artificial intelligence.